Work and Family Balance: An Economic View - Lindy Fursman; Veronica Jacobsen; Jason Varuhas (New Zealand Government, The Treasury, 2003)
The way in which people balance their work and family responsibilities is becoming increasingly prominent on the policy agenda. This paper uses an economic framework to explore the rationale for government policies to improve work/family balance. It finds that strongest economic grounds for government intervention are the effects that maternal work may have on children. The evidence, however, is not strong, and whether maternal employment helps or harms children depends to a large part on the nature and quality of the childcare the children receive while the parents are at work. A number of policies could be used to promote work/family balance, including leave, childcare, changes to working hours, efforts to improve the family-friendliness of organisational cultures and tax/benefit policies. The most significant factor affecting work/family balance appears to be the organisational culture of the firm. In general, if organisational culture is not, in fact family-friendly, family-friendly measures will have little effect.
Keywords: D21; J13; J33; J38; I31; L29; 330; work-life balance; work-family balance; organisational culture; public policy; workplace regulation; labour market regulation; family; family policy; childcare; parental leave; working hours; firm